Bearing capacity and damage behavior of HCFTST columns under cyclic loading. (August 2021) - Wang, Jian-Tao; Wu, Xiao-Hong; Yang, Bin; Sun, Qing
Abstract: This paper conducted a comprehensive study on the bearing capacity and damage behavior of circular high-strength concrete-filled thin-walled steel tubular (HCFTST) columns based on the quasi-static seismic test. The moment-axial force relationship was first analyzed in fiber element method, and the influences of key parameters including the peak strain of concrete, material strengths and diameter-to-thickness ( D / t ) ratios were investigated to develop a practical design method. Then, a dependent triaxiality fracture criterion of high-strength (HS) steel was introduced to establish the finite element damage model for revealing the seismic damage behavior of HCFTST columns, and subsequently a modified restoring force model based on the truss mechanism and the unified theory of concrete-filled steel tube was established and verified. The result indicates that: increasing the steel yield strength, reducing the concrete strength as well as the D / t ratio could respectively push the moment-axial force curves moving inward; the proposed parabolic moment-axial force curve agreed well with the tested bearing capacity; the HS steel tube generated a deep plasticity accumulation to induce the ductile fracture, and the concrete damage area appeared in a V-shaped distribution; increasing the axial compression ratios and D / t ratios amplified the fracture damage of the steel tube web; the established restoring force model displayed a comparatively reasonable accuracy on the degradation behavior (e.g., bearing capacity and stiffness) and the hysteretic characteristic (e.g. softening platform). The aforementioned study could provide the meaningful references for the design and seismic analysis of HCFTST columns.